2007
DOI: 10.1111/j.1600-0501.2006.01306.x
|View full text |Cite
|
Sign up to set email alerts
|

A 10‐year prospective study of ITI dental implants placed in the posterior region. I: Clinical and radiographic results

Abstract: ITI dental implants placed in the posterior jaw demonstrate excellent long-term clinical success. Hollow-cylinder implants seem to display a higher risk for crestal bone loss. Recession depth and attachment levels appear to be good clinical indicators of peri-implant bone loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
116
1
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(159 citation statements)
references
References 29 publications
18
116
1
9
Order By: Relevance
“…Similarly, Papavasiliou et al (10) demonstrated that oblique forces increased the stress concentration in the implant and bone. These results are also in accordance with the literature that describes the influence of increase in crown height on the transference of occlusal forces (9,11,13,15,(18)(19)(20)(21)(22)(23)(24).…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, Papavasiliou et al (10) demonstrated that oblique forces increased the stress concentration in the implant and bone. These results are also in accordance with the literature that describes the influence of increase in crown height on the transference of occlusal forces (9,11,13,15,(18)(19)(20)(21)(22)(23)(24).…”
Section: Discussionsupporting
confidence: 82%
“…The correct implant position and inclination were established with a surgical guide, and a conventional 2-step technique was used (Blanes et al, 2007). After 1 week, RDPs were adjusted and relined with resilient soft lining material (Ufi Gel P; Voco, Cuxhaven, Germany) for use during the 4-month osseointegration period.…”
Section: Clinical Proceduresmentioning
confidence: 99%
“…Several clinical studies indicated a maximum probe penetration of 3 mm for successful implants [15,46,48,51]. The two year longitudinal study of Brägger et al [13] confirmed that the measurements of probing attachment level (PAT) along with radiographic parameters were good predictors of peri-implant bone level.…”
Section: Other Predictors Of Bone Loss and Implant Successmentioning
confidence: 52%